STUDY OF THE PARAMETERS OF TOLERABILITY AND ADHERENCE TO THERAPY IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND ARTERIAL HYPERTENSION ON THE BACKGROUND OF TREATMENT WITH FIXED COMBINATION OF RAMIPRIL AND AMLODIPINE (ACCORDING TO THE RESULTS OF OBSERVATIONAL STUDY "GRANAT-2") - S. Y. Martsevich; Yu. V. Lukina; N. P. Kutishenko; V. P. Voronina; N. A. Dmitrieva; A. V. Zakharova; O. V. Lerman; A. A. Garganeyeva; T. A. Gomova; S. A. Drozdetsky; A. I. Chesnikova (Рациональная фармакотерапия в кардиологии)
Working group of the “GRANAT-2” study: Tula - Trubitsyn G.I., Ivanov Yu.V., Mirenkova O.K., Eskova R.A., Simonova R.P., Milon M.E., Telegina E.V., Kuznetsov A.M., Zhukova N.A., Zainullina I.K.; Rostov-on-Don - Budanov O.V., London E.M., Minosyan L.V., Nedashkovskaya N.G., Ter-Ananyants Ye.A.; Tomsk - Proskokova I.Yu., Permyakova O.V., Politova L.V., Maneeva I.D., Ivanova S.Yu.; Nizhny Novgorod - Larina O.V., Pokrovskaya I.N., Patselt E.A.; Moscow - Sladkova T.A., Zelenova Т.V. Aim. To study the tolerability and adherence to antihypertensive therapy in patients with hypertension and chronic obstructive pulmonary disease (COPD) using the fixed combination of ramipril and amlodipine in the observational program for patients with arterial hypertension and COPD (GRANAT-2). Material and methods. Patients with hypertension and COPD (n=52) with all inclusion criteria and without exclusion criteria who signed informed consent to participate in the GRANAT-2 program were included into the study. The use of a fixed combination of ramipril and amlodipine was recommended in all patients. The doses were determined by the treating physicians in accordance with the official drug instruction. The patients had 4 visits, and the duration of the study was 5 months. The Morisky-Green test was used to assess an adherence of patients to treatment. Assessments of blood pressure, adverse events were performed at all visits. Results. 50 of 52 patients completed the study: 45 patients used the studied fixed combination in the recommended doses, and 5 patients used other antihypertensive drugs, 2 patients withdrew from the study. Systolic blood pressure after 1 month of treatment decreased by an average of 20 mm Hg from the baseline, and diastolic blood pressure – by 10 mmHg. These rates after 5 months of therapy were 29 mm Hg and 15 mm Hg, respectively. Target blood pressure level was achieved in all patients. Increase in adherence of patients to treatment (according to the Morisky-Green test from 21.1% to 65.1%) was found. 2 cases of adverse events (dry cough) were registered. The discrepancy in adherence assessment was revealed between the results from the Morisky-Green test and the data from program case report forms. Conclusion. Regular patient visits to the doctor and the rapid achievement of an antihypertensive effect with good tolerability of a fixed combination of ramipril and amlodipine contributed to the increase in adherence of patients to treatment. Undesirable effects of the drug therapy are significant, but not leading factors that have a negative impact on the patient adherence to treatment.